Managing the Embedded Multinational: A Business Network View - Dhanaraj, Charles (Journal of International Business Studies, 2007)
It has long been recognized that controlling complex organizations like multinational enterprises (MNEs) is a multi-dimensional problem. Efficient organizational structures based on Coasian transaction costs often run afoul of individual or sub-unit goals, resulting in vertical conflicts between headquarters and subsidiaries (Nohria and Ghoshal, 1994). Further, horizontal competition among subsidiaries intent on promoting their own strategic agendas within the MNE results in internecine competition over resources and consequent rents (Mudambi and Navarra, 2004). Thus, the resulting organization and control structures of MNEs are the outcome of political processes where ‘power explains results when the organization sacrifices efficiency to serve special interests’ (Williamson and Ouchi, 1981).